KARST WATER RESOURCES AND GEO-ECOLOGY IN TYPICAL REGIONS OF CHINA - Lu Ya. (My University, 2007)
The aim of this work is to compare the different karst water features and related water resources in South and North China. In Southern China there are over 3,358 karst ground river systems with a total discharge of about 420 × 108 m3 in the dry season. In North China, there are about 100 larger karst spring systems, each with a catchment area from 500 km2 to over 4,000 km2, and an average discharge from 1 to 13 m3/s. The basic geo-ecological features of water, soil and air quality are described for typical karst regions of China. The total quality of geo-ecology is evaluated by five important factors.
Keywords: KARST; WATER RESOURCES; GEOECOLOGY; CHINA